Model Linier Diperumum Untuk Memodelkan Durasi Curah Hujan Tinggi di Sulawesi SelatanSelatan - Husain, Ahmad; Isma Muthahharah; Amran (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to model the duration of high rainfall in South Sulawesi which causes hydrological disasters in January each year. In this study, climate data such as rainfall, wind speed, relative humidity, sunshine and air temperature were recapitulated and modeled using a generalized linear model. The aim is to predict the relevant variables influencing the increase in the duration of high intensity rains in South Sulawesi. In the parameter estimation process, the generalized linear model is added with a random component in the form of spatial random effects and estimated using a Bayesian approach. The results of the analysis produce which climate variables are relevant to modeling the increase in high rainy days in January, as well as the distance of influence of these relevant variables.